2009
DOI: 10.1158/0008-5472.can-08-1547
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor and PTEN Modulate Tissue Factor Expression in Glioblastoma through JunD/Activator Protein-1 Transcriptional Activity

Abstract: Hypoxia and necrosis are fundamental features of glioblastoma (GBM) and their emergence is critical for the rapid biological progression of this fatal tumor; yet, underlying mechanisms are poorly understood. We have suggested that vaso-occlusion following intravascular thrombosis could initiate or propagate hypoxia and necrosis in GBM. Tissue factor (TF), the main cellular initiator of coagulation, is overexpressed in GBMs and likely favors a thrombotic microenvironment. Epidermal growth factor receptor (EGFR)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 40 publications
(58 reference statements)
5
100
0
2
Order By: Relevance
“…Consistently with this notion the loss of PTEN tumor suppressor resulting in AKT activation was found to drive TF upregulation and procoagulant phenotype in glioma cells especially under hypoxic conditions [62][63][64]. TF is also upregulated by other oncogenic kinases, such as SRC [65] and MET [66].…”
mentioning
confidence: 58%
“…Consistently with this notion the loss of PTEN tumor suppressor resulting in AKT activation was found to drive TF upregulation and procoagulant phenotype in glioma cells especially under hypoxic conditions [62][63][64]. TF is also upregulated by other oncogenic kinases, such as SRC [65] and MET [66].…”
mentioning
confidence: 58%
“…In cancer cells, the effects of oncogenic EGFR on TF are mediated through an NFκB dependent mechanism [10], as well as by processes involving AP-1 and c-Jun Nterminal kinase (JNK) activation [12]. Since, the TF promoter also contains functional sites for other transcription factors, including SP1 and Egr-1, other pathways may also be involved downstream of EGFR [26].…”
Section: Discussionmentioning
confidence: 99%
“…Activated K-ras and members of the ErbB family, such as epidermal growth factor receptor (EGFR) and EGFRvIII all upregulate TF on the surface of cancer cells [10][11][12] and trigger the release of TF-containing microvesicles into the circulation of tumour bearing mice [7,10]. These events contribute to tumour formation and angiogenesis by causing changes in the expression of angiogenic factors [7], or through their impact on tumour initiation [10].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental models of tumor development, as well as human cancer materials, link TF to the aggressiveness of several malignancies, including gliomas (5)(6)(7). TF induction in cancer cells may be driven by oncogenetic events, e.g., through EGF receptor (EGFR) and its mutant, EGFRvIII, and inactivation of the tumor suppressor PTEN (6,(8)(9)(10). Other reports have suggested that TF may be triggered by hypoxia through the transcription factor Early growth response gene-1 (11).…”
mentioning
confidence: 99%